Banker to the poor : The story of muhammad yunus and the founding of the grameen bank and grameen family of companies - Yunus, Muhammad (Social entreprenurship series)
In this program Yunus describes how he created microfinance-collateral-free lending and savings and other business services to the poorest citizens.